2005
DOI: 10.1002/jmv.20311
|View full text |Cite
|
Sign up to set email alerts
|

Increased hepatocarcinogenic potential of hepatitis B virus genotype A in Bantu‐speaking sub‐saharan Africans

Abstract: Genotypes A, D, and E of the hepatitis B virus (HBV) circulate in southern Africa, with genotype A predominating. Their hepatocarcinogenic potential in Bantu-speaking sub-saharan Africans is, however, unknown. Using a case/control format, we investigated the hepatocarcinogenic potential of these genotypes and subgenotype A1 of genotype A, which accounts for the great majority of genotype A isolates. HBV isolates from 111 unselected Bantu-speaking sub-saharan Africans with hepatocellular carcinoma (HCC) and 111… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
114
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(121 citation statements)
references
References 43 publications
(76 reference statements)
5
114
2
Order By: Relevance
“…The majority of genotype A strains from our patients (86%) were found to be Ae; they were probably introduced to Japan by immigrants and visitors from foreign countries [Kobayashi et al, 2004]. Cirrhosis and hepatocellular carcinoma developed in only one of the 19 (5%) patients infected with subgenotype Ae, in remarkable contrast to frequent hepatocellular carcinoma in Africa where infection with subgenotype Aa is common during the infancy [Kew et al, 2005].…”
Section: Discussionmentioning
confidence: 68%
“…The majority of genotype A strains from our patients (86%) were found to be Ae; they were probably introduced to Japan by immigrants and visitors from foreign countries [Kobayashi et al, 2004]. Cirrhosis and hepatocellular carcinoma developed in only one of the 19 (5%) patients infected with subgenotype Ae, in remarkable contrast to frequent hepatocellular carcinoma in Africa where infection with subgenotype Aa is common during the infancy [Kew et al, 2005].…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, genotypes A and B have been reported to be associated with an earlier seroconversion from HBeAg to anti-HBe than genotypes C and D (5,16). However, in a study from South Africa, subgenotype A1 was associated with a higher risk for HCC than other subgenotypes of A or non-A genotypes (14). Genotype impact on treatment outcome is more uncertain, but genotype B has been shown to respond better to alpha interferon treatment than genotype C (13,30).…”
Section: Discussionmentioning
confidence: 99%
“…HBV/A is mainly distributed in Africa (HBV/A1), the United States of America, and Europe (HBV/A2). Several reports from Africa, India, and Brazil have shown that HBV/A1 is associated with a high incidence of HCC in younger patients without cirrhosis [22] . By contrast, HBV/A2 is reported to be associated with a lower incidence of HCC than HBV/D and HBV/ F [23,24] .…”
Section: Mutationsmentioning
confidence: 99%